Characterization of a new Staphylococcus aureus Kayvirus harboring a lysin active against biofilms - Melo, Luís Daniel Rodrigues (2018)
Staphylococcus aureus is one of the most relevant opportunistic pathogens involved in many biofilm-associated diseases, and is a major cause of nosocomial infections, mainly due to the increasing prevalence of multidrug-resistant strains. Consequently, alternative methods to eradicate the pathogen are urgent. It has been previously shown that polyvalent staphylococcal kayviruses and their derived endolysins are excellent candidates for therapy. Here we present the characterization of a new bacteriophage: vB_SauM-LM12 (LM12). LM12 has a broad host range (>90%; 56 strains tested), and is active against several MRSA strains. The genome of LM12 is composed of a dsDNA molecule with 143,625 bp, with average GC content of 30.25% and codes for 227 Coding Sequences (CDSs). Bioinformatics analysis did not identify any gene encoding virulence factors, toxins, or antibiotic resistance determinants. Antibiofilm assays have shown that this phage significantly reduced the number of viable cells (less than one order of magnitude). Moreover, the encoded endolysin also showed activity against biofilms, with a consistent biomass reduction during prolonged periods of treatment (of about one order of magnitude). Interestingly, the endolysin was shown to be much more active against stationary-phase cells and suspended biofilm cells than against intact and scraped biofilms, suggesting that cellular aggregates protected by the biofilm matrix reduced protein activity. Both phage LM12 and its endolysin seem to have a strong antimicrobial effect and broad host range against S. aureus, suggesting their potential to treat S. aureus biofilm infections.